Ultra-low power energy harvesting wireless sensor network design - Zheng, Chenyu (Kansas State University, 2015)
This thesis presents an energy harvesting wireless sensor network (EHWSN) architecture customized for use within a space suit. The contribution of this research spans both physical (PHY) layer energy harvesting transceiver design and appropriate medium access control (MAC) layer solutions. The EHWSN architecture consists of a star topology with two types of transceiver nodes: a powered Gateway Radio (GR) node and multiple energy harvesting (EH) Bio-Sensor Radio (BSR) nodes. A GR node works as a central controller to receive data from BSR nodes and manages the EHWSN via command packets; low power BSR nodes work to obtain biological signals, packetize the data and transmit it to the GR node. To demonstrate the feasibility of an EHWSN at the PHY layer, a representative BSR node is designed and implemented. The BSR node is powered by a thermal energy harvesting system (TEHS) which exploits the difference between the temperatures of a space suit's cooling garment and the astronaut's body. It is shown that through appropriate control of the duty-cycle in transmission and receiving modes, it is possible for the transceiver to operate with less than 1mW power generated by the TEHS. A super capacitor, energy storage of TEHS, acts as an energy buffer between TEHS and power consuming units (processing units and transceiver radio). The super capacitor charges when a BSR node is in sleep mode and discharges when the node is active. The node switches from sleep mode to active mode whenever the super capacitor is fully charged. A voltage level monitor detects the system's energy level by measuring voltage across the super capacitor. Since the power generated by the TEHS is extremely low(less than 1mW) and a BSR node consumes relatively high power (approximately 250mW) during active mode, a BSR node must work under an extremely low duty cycle (approximately 0.4%). This ultra-low duty cycle complicates MAC layer design because a BSR node must sleep for more than 99.6% of overall operation time. Another challenge for MAC layer design is the inability to predict when the BSR node awakens from sleep mode due to unpredictability of the harvested energy. Therefore, two feasible MAC layer designs, CSA (carrier sense ALOHA based)-MAC and GRI (gateway radio initialized)-MAC, are proposed in this thesis.Balasubramaniam Natarajan
Keywords: Energy harvesting; Wireless sensor network; Ultra-low power; MAC layer design; Electrical Engineering (0544)